Argentina’s Politicized Bureaucracy: A Historical Analysis of Two Political Regimes - Elías, María (Revue Gouvernance / Governance Review, 2017)
This article employs the concept of “bureaucratic authoritarianism” (O’Donnell, 1978, 1988) to evaluate whether the character of Argentine bureaucracy has changed in the shift from dictatorial to democratic rule. A brief discussion about the political and administrative history of that country follows the characterization of bureaucratic authoritarianism in light of accountability and clientelism (Fox, 2000; Smulovitz & Peruzzotti, 2000, 2003). This article explores the possibility of bureaucratic legitimacy in Argentina through the enforcement of the rule of law, the system of checks and balances, and the fair treatment of citizens.